EFFECTIVENESS OF COLD PRESSED JUICE COMBINATION OF RED SPINACH, PINEAPPLE, HONEY AND PIR ON INCREASING HEMOGLOBIN LEVELS IN WOMAN ADOLESCENT - Hasanah, Intan Nugraheni; Ariyanti, Ida; Octaviani, Dhita Aulia (Journal of Applied Health Management and Technology, 2024)
Background: Anemia in young women is still quite high, worldwide the prevalence of diabetes is estimated at between 40% and 88%. Prevalence of anemia among young people in developing countries is about 27%, while in developed countries around 6%, the incidence of anemia often affects the young women due to stress and menstruation. Red spinach has a higher iron content rather than other leafy vegetables. The Â honey pineapple contains bromelain which is useful in boosting the body's immune system. The pears contain antioxidants that are useful for fighting inflammation. Methods: This study used a quasi experimental approach with a pretest posttest design. The study population consisted of students from the Semarang Health Ministry's Polytechnic majoring in midwifery with a sample of 15 people in the treatment group. Respondents previously measured their Hb first and then given treatment from the first day to the seventh day. On the 8th day Hb is measured again. The sampling technique used consecutive sampling. The research instrument used a digital Hb meter and checklist. Results: As a result, the mean hemoglobin level of the treatment group before the combination of time count, pineapple honey and cold fruit juice was 13.32 g/dL, the lowest value is 11, 3 g/dL, the highest value is 15.7 g. /dl, and the mean hemoglobin level after treatment was 11.8 g/dl. dl, the lowest is 11.8 gr/dl, the highest is 15.8 gr/dl. Test results with independent t-test in p-value of 0.003 (<0.005), so Ho is rejected and Ha is accepted giving of cold pressed juice combination red spinach pineapple honey and pears are effective within increasing hemoglobin levels in woman adolescents. Conclusion:. The cold pressed juice are the combination of red spinach and honey pineapple that increased hemoglobin on young women. The preventive and promotive efforts can be used through consumeing the iron food and some of foods, so that the adolescent nutrients fulfilled. The results of this study should provide information about childbirth and community health, provide future research, and be used for research. Hopefully, next researcher can discover new innovations, such as combinations of different foods that can increase blood hemoglobin levels.